Physicochemical differentiation of lard and fats of beef and chicken - Abbasiliasi, Sahar; Azir, Marliana; Tan, Joo Shun; Ibrahim, Tengku Azmi; Sazili, Awis qurni; Mustafa, Shuhaimi (Hibiscus Publisher Enterprise, 2024)
This study differentiates, based on their physicochemical properties, the fats of pork, beef and chicken. Fats from the three animal species were extracted and assessed for their iodine, peroxide and acid values and moisture/volatile matter contents. Triacylglycerol (TAG) and fatty acid compositions of the oils were determined, and their structural and thermal properties analysed. Results showed that chicken fat had higher iodine value compared to that of lard and beef fat indicating that avian fat has more double bonds and less oxidative stability. There was no significant difference (P>0.05) between the acid values of lard and beef fat. Similarly, there was no significant differences (P>0.05) either in the moisture/volatile matter content of lard, and fats of beef and chicken. Highest unsaturated fatty acids were present in chicken fat (68%) followed by lard (55.06%) and beef fat (46.86%). Chicken fat has the lowest cooling and melting temperatures (~ -38 oC and ~ -27 oC, respectively). Fourier transform infrared (FTIR) spectrum of beef fat could be differentiated from that of lard and chicken fat in existing peak at frequency ~1127 cm−1. Highest total saturated TAG and fatty acids were observed in beef fat (~84% and ~53%) while chicken fat showed the highest total unsaturated TAGs and fatty acids (~81% and ~68%). Results from this study could serve as a basis for authenticity determination of food products and quantification of adulteration.